Rapid accumulation of CD14+CD11c+ dendritic cells in gut mucosa of celiac disease after in vivo gluten challenge. - Ann-Christin Røberg Beitnes; Melinda Ráki; Margit Brottveit; Knut Erik Aslaksen Lundin; Frode Lars Jahnsen; Ludvig Magne Sollid (PLoS ONE, 2012)
Of antigen-presenting cells (APCs) expressing HLA-DQ molecules in the celiac disease (CD) lesion, CD11c(+) dendritic cells (DCs) co-expressing the monocyte marker CD14 are increased, whereas other DC subsets (CD1c(+) or CD103(+)) and CD163(+)CD11c(-) macrophages are all decreased. It is unclear whether these changes result from chronic inflammation or whether they represent early events in the gluten response. We have addressed this in a model of in vivo gluten challenge.Treated HLA-DQ2(+) CD patients (n = 12) and HLA-DQ2(+) gluten-sensitive control subjects (n = 12) on a gluten-free diet (GFD) were orally challenged with gluten for three days. Duodenal biopsies obtained before and after gluten challenge were subjected to immunohistochemistry. Single cell digests of duodenal biopsies from healthy controls (n = 4), treated CD (n = 3) and untreated CD (n = 3) patients were analyzed by flow cytometry.In treated CD patients, the gluten challenge increased the density of CD14(+)CD11c(+) DCs, whereas the density of CD103(+)CD11c(+) DCs and CD163(+)CD11c(-) macrophages decreased, and the density of CD1c(+)CD11c(+) DCs remained unchanged. Most CD14(+)CD11c(+) DCs co-expressed CCR2. The density of neutrophils also increased in the challenged mucosa, but in most patients no architectural changes or increase of CD3(+) intraepithelial lymphocytes (IELs) were found. In control tissue no significant changes were observed.Rapid accumulation of CD14(+)CD11c(+) DCs is specific to CD and precedes changes in mucosal architecture, indicating that this DC subset may be directly involved in the immunopathology of the disease. The expression of CCR2 and CD14 on the accumulating CD11c(+) DCs indicates that these cells are newly recruited monocytes.